A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) - Moreno, Jhon César Neita; Ratcliffe, Brett C. (Zootaxa, 2017)
A new species of the Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) is described from Colombia, Ecuador, and Guyana along with supporting illustrations and a diagnosis. A checklist of Palaeophileurus species is included with a new country record for Colombia of Palaeophileurus proximus Dechambre.